Histoire graphique de la langue bretonne : la question de la norme - Herve Le Bihan (Lengas)
The history of the Breton spelling begins in the Middle Ages, when the language was then a part of the lingua britannica which gives birth too to Welsh and Cornish. For the next period, the one called Middle Breton (1100-1650), the Breton language leaves the traditionnal spelling to adapt, in part, some graphemes borrowed from French. In the course of the XVIIIth century several dictionaries of Breton will be edited, sometimes with the help of the Breton States, and they will have a significant influence. Le Gonidec, at the beginning of the XIXth century, imposes the first modern spelling standard. This standard will be renewed in 1908, 1936 and 1941. This standard is still in use today, despite some flaws which cannot exceed the fact it is as a standard the most in use today : the schools, the public (or not) medias, the public sphere (as the roads and cities signs or as the official forms). That was possible by a strong social pressure (Diwan’s creation, immersives schools, in 1977, or the Public Office of the Breton Language’s creation in 1999).